2008
DOI: 10.1089/ten.tec.2008.0163
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer and Living Release of Transforming Growth Factor-β3 for Cartilage Tissue Engineering Applications

Abstract: Cartilage restoration continues to present a tremendous clinical challenge due to its nonvascular nature. Many studies have demonstrated that chondrogenesis of progenitor cells can be achieved in vitro by manual dose of growth factors; however, it remains a vital difficulty in feeding growth factors to implanted therapeutic cells in vivo. Herein, we constructed recombinant adenovirus encoding human transforming growth factor-beta3 (hTGF-beta3) and practiced it in rat bone marrow-derived mesenchymal stromal cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…Consequently, different chondrogenesis effects were induced accordingly. Our previous findings (Hao et al, 2008b) suggested a short pharmacological half-life of the directly dosed TGFb3, the release profile of which may lead to various results under different experimental conditions (cell lineage, material, cell cure, or tissue cure and so on) (Hao et al, 2008a;Yao et al, 2010;Zhang et al, 2010). The results from this study indicated that in the functional time of adenovirus, adenovirus-mediated transgenic TGFb3 could provide localized, continuous, and longer term supply of growth factors to the target cells.…”
Section: Discussionmentioning
confidence: 67%
“…Consequently, different chondrogenesis effects were induced accordingly. Our previous findings (Hao et al, 2008b) suggested a short pharmacological half-life of the directly dosed TGFb3, the release profile of which may lead to various results under different experimental conditions (cell lineage, material, cell cure, or tissue cure and so on) (Hao et al, 2008a;Yao et al, 2010;Zhang et al, 2010). The results from this study indicated that in the functional time of adenovirus, adenovirus-mediated transgenic TGFb3 could provide localized, continuous, and longer term supply of growth factors to the target cells.…”
Section: Discussionmentioning
confidence: 67%
“…Different factors have been reported for their ability to direct MSCs toward the chondrocyte phenotype. They include the transforming growth factor beta (TGF-β) [6-11], bone morphogenic proteins (BMPs) [9,10,12,13], the insulin-like growth factor I (IGF-I) [14,15], basic fibroblast growth factor (FGF-2) [16,17], zinc-finger protein 145 (ZNF145) [18], human telomerase (hTERT) [19,20], and the antiapoptotic factor Bcl-xL [21]. Yet, the use of these agents remains disputable, as most of them do not promote the synthesis of specific cartilage matrix components per se (FGF-2, hTERT, Bcl-xL) [16,19-21] or an adequate chondrogenic differentiation (IGF-I) [15], or even lead to undesirable MSC hypertrophy (TGF-β, BMPs) [7,10,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…20 The transforming growth factor-beta (TGF-β) is another highly potent agent capable of promoting cartilage repair, enhancing the proliferation of chondrocytes and production of extracellular cartilage matrix (ECM) components and preventing cartilage degradation. [21][22][23] While gene transfer and overexpression of TGF-β was evaluated in articular chondrocytes in vitro and in situ via nonviral 24,25 and classical viral (adenoviruses and retroviruses) vectors, [26][27][28] the use of such vehicles in vivo may be impaired by their low and short-term efficiencies, especially in nondividing cells like chondrocytes, by the possibility of insertional mutagenesis (retroviral vectors), and their relatively high immunogenicity (adenoviral vectors). 5,6 In marked contrast, recombinant vectors based on the human adeno-associated virus (AAV) exhibit high, extended gene transfer efficiencies in chondrocytes in vitro and in situ within their dense ECM (up to 80% for at least 150 days) 29 due to their small size (~20 nm) and their maintenance as stable episomes, making them particularly adapted for in vivo setups.…”
mentioning
confidence: 99%